IMPLEMENTASI KEBIJAKAN IZIN MENDIRIKAN BANGUNAN PADA DINAS PERUMAHAN, KAWASAN PERMUKIMAN DAN PERTANAHAN KOTA KENDARI - Niluh Putu Rita P.S; Wempy Banga; Suryani BB (Universitas Halu Oleo, 2019)
This study aims to describe and analyze the implementation of the Building Construction Permit at the Housing Office, Settlement Area and Land of Kendari City.This research method uses a type of qualitative descriptive research that is data and information obtained from research informants and documentation relating to the facts then analyzed by connecting between concepts and facts to answer research problemsThe results of the study show that the implementation of the Building Construction Permit in the Housing, Settlement and Land Offices of Kendari City is included in the category of adequate. Policy implementation variables covering organizational aspects, aspects of interpretation and aspects of the application have been carried out adequately.